Project Based Learning, Collective Portfolio and Nutrition: integrating knowledge in Unified Health System - Pereira da Silva, Renato (2023)
Introduction: graduation in the health area should equally contemplate the psychomotor, cognitive and affective domains from the problematization of everyday situations of the Unified Health System (SUS). Objective: to evaluate the training of nutritionists based on the integration of knowledge from the teaching-service-community triad, based on Project-Based Learning (PBL) and Collective Portfolio (PC) in the micropolitics of the SUS. Method: a “baby shower” planned and executed by students, guided by a group of teachers, aimed at pregnant women in the SUS network, providing the live work of the concept-tools “alterity”, “bond”, “welcoming”, and “participatory management” was undertaken. Results: records in the CP showed articulation between different knowledge and learning domains in the training of nutritionists by skills. Conclusion: PBL+CP is a powerful and viable teaching-learning tool for the training of professionals capable of working in SUS integrating teachingservice-community.